ПРО НАБЛИЖЕННЯ ПЛОСКОПАРАЛЕЛЬНОГО ПОЛЯ В РОЗРАХУНКАХ ПЛОСКОМЕРИДІАННИХ ПОЛІВ ПОБЛИЗУ ПЛОСКОЇ ГРАНИЧНОЇ ПОВЕРХНІ - Михайлов, В.М.; Петренко, М.П. (Інститут електродинаміки Національної академії наук України, 2020)
Axisymmetric and plane magnetic and electrostatic fields over plane boundary of conductive half-space are considered. Conductive ring or straight conductor of the same section with high frequency or pulse current creates magnetic fields. There is sharp skin-effect in conductor. The same, but charged, conductors create electrostatic field. The ring and straight conductor are represented by assemblages of elementary current-carrying or charged rings and axes. Formulation of axisymmetric and plane magnetic field vector potential problems for elementary currents over perfectly superconductive half-space and its solutions are described. Currents and charges inducted in conductive half-space are calculated. The comparison of magnetic field induction and electrostatic field strength distributions on boundary surface is made. The criterion of plane field approximation for calculation of axisymmetric magnetic and electrostatic fields is proposed and its allowable values are defined. It’s established that for some values of this criterion the axisymmetric electrostatic field strength distribution of boundary of conductive half-space approach to the axisymmetric magnetic field induction distribution on boundary of perfectly superconductive half-space. References 9, figures 4.